Digital transformation at the Grand Egyptian Museum - Nancy Ali; Ayman El-Sayed; Amr Abdel Nasser (Cybrarians Journal)
The Grand Egyptian Museum (GEM) represents a transformative addition to Egypt's cultural and heritage landscape, set to redefine the traditional museum experience through immersive, interactive, and technology-driven exhibits. As the largest museum globally dedicated to ancient Egypt, the GEM aspires to inspire future generations, fostering creativity and innovation while addressing the scarcity of cultural institutions in Egypt. Its extensive collection spans over 700,000 years, featuring thematic exhibits that narrate the evolution of Egyptian society, religion, and governance.